Risk of Upper Extremity Musculoskeletal Injury in Laparoscopy Training - Prasetyono, Theddeus OH; Andrian, Christopher R; Kinanthi, Elisabet LA (UI Scholars Hub, 2022)
Introduction. The laparoscopy procedure still has an ergonomic burden that can increase the risk of musculoskeletal injury, especially in the upper extremity. Furthermore, the risk is compounded in laparoscopic training as the trainees have to repeat the same movements many times to achieve competencies. This study revealed the relation between the position and the risk of musculoskeletal injury in laparoscopy training. Methods. A cross-sectional study on nine subjects was conducted during laparoscopy training. By fixing the table height at 77 cm, we measured the operator height and upper extremity positions to relate them to their VAS and DASH scores. Results. The overall ratio of table height to subject height was Conclusions. There is a risk of upper extremity musculoskeletal injury without disabilities. The pain produced by laparoscopy activity has shown to be mild and needs no medication. The wrist position is considered the highest risk of initiating the upper extremity injury.